Age-adjusted Charlson comorbidity score is associated with the risk of empyema in patients with COPD. Issue 36 (September 2017) - Ho, Chung-Han; Chen, Yi-Chen; Chu, Chin-Chen; Wang, Jhi-Joung; Liao, Kuang-Ming
Abstract : Abstract: Patients with chronic obstructive pulmonary disease (COPD) have a higher risk of pneumonia than the general population due to their impaired lung defense. They also have a higher risk of empyema and more comorbidities than patients without COPD. This study aimed to evaluate the risk of empyema in patients with COPD after adjusting for age and comorbidities using the age-adjusted Charlson comorbidity index (ACCI). Data were retrieved from the National Health Insurance Research Database. COPD patients were defined as inpatients aged >40 years with an International Classification of Diseases, Ninth Revision, Clinical Modification diagnosis code for COPD. In total, 558, 660 COPD patients were enrolled and separated into 3 groups by ACCI score to represent the severity of comorbidity (⩽2, 3–5, and >5). Other comorbidities assessed included autoimmune diseases, gastroesophageal reflux disease, dyslipidemia, chest wall injury, and thoracostomy. Of the 558, 660 patients, 36, 556 (6.54%) had low ACCI scores (⩽2), 208, 292 (37.28%) had moderate ACCI scores (3–5), and 313, 812 (56.17%) had high ACCI scores (>5). The mean ages of the low, moderate, and high groups were 50.66, 70.62, and 78.05 years, respectively. The hazard ratio (HRs) for empyema were 1.26 (95% confidence interval (CI) = 1.13–1.40) in the moderate ACCI group and 1.55 (95% CI = 1.39–1.72) in the high ACCI group compared with the low ACCI group. The overall incidence of empyema in COPD patients was 2.57 per 1000 person-years. This is the first study to use ACCI scores to analyze the risk of empyema in patients with COPD. Patients with high ACCI scores were older and had more complicated comorbidities, resulting in a higher risk of empyema and poor prognosis. The subgroup analysis indicated that COPD patients with comorbid autoimmune disease, gastroesophageal reflux disease, chest wall injury, or history of thoracostomy did not have a higher risk of empyema than patients without these comorbidities. Empyema is an important issue in patients with COPD and is associated with significant morbidity and mortality. Awareness of the risk factors for empyema, close monitoring, and early intervention may improve patient outcomes and decrease mortality.